2021
DOI: 10.1002/ente.202000886
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Influence of Particle Shape on Mechanical Compression and Effective Transport Properties in Granular Lithium‐Ion Battery Electrodes

Abstract: The calendering step during manufacturing of lithium‐ion batteries is an essential process in the production, as it significantly influences the microstructure of electrodes and, therefore, the performance of the battery. Within this context, this article investigates the influence of particle shapes on the micromechanical responses during calendering and, in turn, their impact on the effective transport properties of battery electrodes. The electrodes are modeled using discrete elements. For this reason, a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Moreover, the contact stress and contact radius increase with the progress of Li-ion intercalation.The increase in the contact radius as the charge progresses can provide an explanation for the decrease in battery resistance during the charging process, 34 because the electronic conductivity between active particles is related to the contact radius. 35 In the early stage of charging (τ = 1), the contact radius and contact stress of the contact surface of the AM particles are relatively small. Therefore, at this time, the stress has little effect on the Li-ion concentration distribution, which leads to almost the same Li-ion concentration distribution in the contact direction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the contact stress and contact radius increase with the progress of Li-ion intercalation.The increase in the contact radius as the charge progresses can provide an explanation for the decrease in battery resistance during the charging process, 34 because the electronic conductivity between active particles is related to the contact radius. 35 In the early stage of charging (τ = 1), the contact radius and contact stress of the contact surface of the AM particles are relatively small. Therefore, at this time, the stress has little effect on the Li-ion concentration distribution, which leads to almost the same Li-ion concentration distribution in the contact direction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lippke et al [ 57 ] modeled the structure formation during drying using the discrete element method (DEM) by using surrogate models for relevant fluid effects and could predict the coating porosity for different mass loadings. As most electrode microstructural simulations focus on spherical particles, Becker et al [ 58 ] Modeled the influence of particle shape on the mechanical compression and resulting transport properties of electrodes for non‐spherical particles, using a novel random close packing algorithm.…”
Section: Modeling Simulation and Tomographymentioning
confidence: 99%
“…The microstructure–property relations can be assessed by various types of numerical simulations. The discrete element method (DEM) has been used to model granular microstructures and corresponding transport properties. ,, By using a resistor network method, Birkholz et al investigated the effective conductivity of granular electrode structures considering the pore phase and overlapping spheres, leading to a better understanding of granular microstructures on effective transport properties. , Using high-fidelity DEM simulations, Srivastava et al showed that electrode microstructures with tailored transport properties can be generated by controlling the CBD cohesive forces and AM-CBD adhesive forces . Zielke et al reconstructed 3D battery cathodes by combining the AM phase characterized by XCT and used two modelsa random cluster model and a fiber modelto generate a virtual CBD phase.…”
Section: Introductionmentioning
confidence: 99%